International study of childhood leukemia in residences near electrical transformer rooms - Crespi, Catherine M.; Sudan, Madhuri; Juutilainen, Jukka; Roivainen, Päivi; Hareuveny, Ronen; Huss, Anke; Kandel, Shaiela; Karim-Kos, Henrike E.; Thuróczy, György; Jakab, Zsuzsanna; Spycher, Ben D.; Flueckiger, Benjamin; et al. (Environmental research, 2024)
New epidemiologic approaches are needed to reduce the scientific uncertainty surrounding the association between extremely low frequency magnetic fields (ELF-MF) and childhood leukemia. While most previous studies focused on power lines, the Transformer Exposure study sought to assess this association using a multi-country study of children who had lived in buildings with built-in electrical transformers. ELF-MF in apartments above built-in transformers can be 5 times higher than in other apartments in the same building. This novel study design aimed to maximize the inclusion of highly exposed children while minimising the potential for selection bias. We assessed associations between residential proximity to transformers and risk of childhood leukemia using registry based matched case-control data collected in five countries. Exposure was based on the location of the subject's apartment relative to the transformer, coded as high (above or adjacent to transformer), intermediate (same floor as apartments in high category), or unexposed (other apartments). Relative risk (RR) for childhood leukemia was estimated using conditional logistic and mixed logistic regression with a random effect for case-control set. Data pooling across countries yielded 16 intermediate and 3 highly exposed cases. RRs were 1.0 (95% CI: 0.5, 1.9) for intermediate and 1.1 (95% CI: 0.3, 3.8) for high exposure in the conditional logistic model. In the mixed logistic model, RRs were 1.4 (95% CI: 0.8, 2.5) for intermediate and 1.3 (95% CI: 0.4, 4.4) for high. Data of the most influential country showed RRs of 1.1 (95% CI: 0.5, 2.4) and 1.7 (95% CI: 0.4, 7.2) for intermediate (8 cases) and high (2 cases) exposure. Overall, evidence for an elevated risk was weak. However, small numbers and wide confidence intervals preclude strong conclusions and a risk of the magnitude observed in power line studies cannot be excluded. •Novel study of childhood leukemia risk and apartments near electrical transformers.•Transformers are a source of high extremely low frequency magnetic fields.•Exposure based on subject's apartment location relative to built-in transformers.•There was little indication of elevated childhood leukemia risk.•Risk of magnitude observed in power line studies cannot be excluded.